Integrated interfacial design of covalent organic framework photocatalysts to promote hydrogen evolution from water - He, Ting (2023)
Attempts to develop photocatalysts for hydrogen production from water usually result in low efficiency. Here we report the finding of photocatalysts by integrated interfacial design of stable covalent organic frameworks. We predesigned and constructed different molecular interfaces by fabricating ordered or amorphous π skeletons, installing ligating or non-ligating walls and engineering hydrophobic or hydrophilic pores. This systematic interfacial control over electron transfer, active site immobilisation and water transport enables to identify their distinct roles in the photocatalytic process. The frameworks, combined ordered π skeletons, ligating walls and hydrophilic channels, work under 300-1000 nm with non-noble metal co-catalyst and achieve a hydrogen evolution rate over 11 mmol g-1 h-1, a quantum yield of 3.6% at 600 nm and a three-order-of-magnitude-increased turnover frequency of 18.8 h-1 compared to those obtained with hydrophobic networks. This integrated interfacial design approach is a step towards designing solar-to-chemical energy conversion systems.